MENA Regional Brief - World Bank (Washington, DC, 2013)
The process of political change and transition across much of the Middle East and North Africa (MENA) continued into 2013, with a great degree of heterogeneity across countries. Violence in Syria has escalated, with spillover effects to Lebanon and Jordan. Security in Yemen is fragile but a national dialogue has started which includes the drafting of a new constitution in advance of national elections. In MENA's transitioning countries drafting of new constitutions remains a critical pending issue. Citizens have not been silent. Their voices continue to be heard across the region calling for greater public participation and open government